Personal Experience and Interpersonal Communication as Predictors of Students’ Social Interaction - Monalisa Monalisa; Yogi Damai Syaputra; Bilqis Raudlatul Anin Nabila; Lifna Alfiyanah (Jurnal Counseling Care, 2026)
Social interaction is one of the important developmental competencies for students as they navigate academic and social life in higher education. However, poor social interaction can hinder students' adjustment and personal development. This study aims to analyze the relationship between personal experience and interpersonal communication in students' social interaction. The study used a quantitative correlational design. The research sample consisted of 454 active students from Sultan Maulana Hasanuddin State Islamic University, Banten, selected using convenience sampling. The instruments used included the Personal Experience Checklist (PECK), an interpersonal communication scale, and a social interaction scale. Data were analyzed using Pearson product-moment correlation and multiple correlations. The results showed that personal experience was significantly related to students' social interaction (r = 0.465; p < 0.05) with a moderate level of relationship. Interpersonal communication also had a significant relationship with social interaction (r = 0.393; p < 0.05), with a weak level of relationship. Simultaneously, personal experience and interpersonal communication contributed significantly to students' social interaction (R = 0.591; p < 0.05), accounting for 35% of the variance. These findings confirm that personal experiences and interpersonal communication skills are important factors in the development of students' social interactions. This research has implications for guidance and counseling services in higher education institutions, enabling them to design preventive and intervention programs that strengthen positive experiences and interpersonal communication among students.